PENINGKATAN PEMBELAJARAN PUKULAN FOREHAND DALAM PERMAINAN TENIS MEJA MELALUI MODIFIKASI ALAT PEMBELAJARAN - Erlan, U.; Supriatna, Eka; Purnomo, Edi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Learning Games Table Tennis Forehand Blow Through Modification Tool Learning In Primary School Grade V students. This study saw an increase table tennis forehand game modification tools through fifth grade students learning in elementary school. population is 120 students, drawn 20% of the total population that is 24 people, using research methods class action research. Data collection techniques obtained by testing motor skills forehand individually using the observation instrument assessment rubric. Data collection tool table tennis, table tennis ball, whistle, duct tape, chalk, and alata written form. Data processing formulas used